2016
DOI: 10.1021/acsami.6b04732
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chemical Force Microscopy for Finding Selective Functional Groups for Discriminating Different Electronic Type Single-Walled Carbon Nanotubes

Abstract: We recently reported a noncovalent chemistry bead-based method that can sort single-walled carbon nanotubes (SWNTs) to ultrahigh purity. The method is based on the higher affinity of functionalized agarose beads for M­(etallic) carbon nanotubes in acidic pH versus S­(emiconducting) SWNTs based on the selective charge reversal of metallic carbon nanotubes. However, fundamental understanding of the relative selective affinity of various functional groups for certain electronic type nanotubes remains somewhat lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Friddle et al 33 performed a direct measurement on adhesive force to understand the interactions between CNTs and chemical functional groups using atomic force microscope probes functionalized with specific functional groups. Wang et al 34 investigated the non-covalent interaction force between several types of different functionalized compounds and single-walled CNTs. It indicated that the amino-terminated alkane has a higher interaction force with the single-walled CNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Friddle et al 33 performed a direct measurement on adhesive force to understand the interactions between CNTs and chemical functional groups using atomic force microscope probes functionalized with specific functional groups. Wang et al 34 investigated the non-covalent interaction force between several types of different functionalized compounds and single-walled CNTs. It indicated that the amino-terminated alkane has a higher interaction force with the single-walled CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…7,13,18,24,28,32,[35][36][37][38][39][40][41][42] However, a direct experimental evidence of the interaction between CNTs and polymer before and after the composite preparation is still lacking. 17,33,34,[43][44][45] In this article, amino functionalized CNTs (NH 2 -CNTs) and hydroxyl functionalized CNTs (OH-CNTs), which are supposed to form different interfaces between CNTs and epoxy resin in composites, were investigated, and pristine CNTs (p-CNTs) were used for reference. We try to reveal the physical and chemical forces between CNTs and epoxy molecules through several methods, such as surface energy analysis (SEA), atomic force microscopy (AFM), and differential scanning calorimetry (DSC).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Because these amine reagents functionalize hydroxyl groups on the highly oxidized surface, this fabrication method cannot be applied to flexible polymerics ubstrates. Most reports on flexible TFTsu sing s-SWCNTsr elied on specialized techniques such as aerosold epositions [7] or transfer processes. [8] Therefore, it is essential to develop an NH 2 -terminated surface on polymerics ubstrates to fabricate SWCNT thinf ilms.…”
mentioning
confidence: 99%